Prognostic Factors Associated With Surviving Less Than 3 Months vs Greater Than 3 Years Specific to Spine Stereotactic Body Radiotherapy and Late Adverse Events. Issue 5 (20th January 2021) - Zeng, K Liang; Sahgal, Arjun; Tseng, Chia-Lin; Myrehaug, Sten; Soliman, Hany; Detsky, Jay; Atenafu, Eshetu G; Lee, Young; Campbell, Mikki; Maralani, Pejman; Husain, Zain A
Abstract: BACKGROUND: Patient selection is critical for spine stereotactic body radiotherapy (SBRT) given potential for serious adverse effects and the associated costs. OBJECTIVE: To identify prognostic factors associated with dying within 3 mo, or living greater than 3 yr, following spine SBRT, to better inform patient selection. METHODS: Patients living ≤3 mo after spine SBRT and >3 yr after spine SBRT were identified, and multivariable regression analyses were performed. We report serious late toxicities observed, including vertebral compression fractures (VCF) and plexopathy. RESULTS: A total of 605 patients (1406 spine segments) were treated from 2009 to 2018. A total of 51 patients (8.4%) lived ≤3 mo, and 79 patients (13%) survived >3 yr. Significant differences in baseline features were observed. On multivariable analysis, nonbreast/prostate primaries (odds ratio [ORs]: 28.8-104.2, P = .0004), eastern cooperative oncology group (ECOG) ≥2 (OR: 23.7, 95% CI: 3.2-177, P = .0020), polymetastatic disease (OR: 6.715, 95% CI: 1.89-23.85, P = .0032), painful lesions (OR: 3.833-8.898, P = .0118), and paraspinal disease (OR: 2.874, 95% CI: 1.118-7.393, P = .0288) were prognostic for ≤3 mo survival. The 3- and 5-yr rates of VCF were 10.4% and 14.4%, respectively, and 3- and 5-yr rates of plexopathy were 2.2% and 5.1%, respectively. A single duodenal perforation was observed, and there was no radiation myelopathy events. CONCLUSION: Shorter survival after spine SBRT was seen in patients with less radiosensitive histologies (ie, not breast or prostate), ECOG ≥2, and polymetastatic disease. Pain and paraspinal disease were also associated with poor survival. Fractionated spine SBRT confers a low risk of late serious adverse events. Graphical Abstract: